Analisis Break Even Point Pada Usaha Yamote Banana di Kecamatan Rantepao Kabupaten Toraja Utara - Pundissing, Rati; Ramba, Dina; Kannapadang, Dwibin (UKI Toraja Press, 2022)
This study aims to determine how the perception of the break even point in the Yamote Banana business in Rantepao District, North Toraja Regency. This type of research is descriptive quantitative research and data collection techniques carried out in this research are field research and library research. Data collection procedures were carried out by means of observation, interviews, and documentation. The results obtained regarding the BEP in the Yamote Banana business are, sales that must be achieved by Yamote Banana as many as 831 units with (chocolate banana nuggets 327 units, banana greentea nuggets 193 units, greentea flavored drinks 189 units and cappuccino flavored drinks 122 units). Thus, Yamote Banana's business in 2020 has reached a break-even point with sales of 7,800 chocolate nugget bananas, 4,680 greentea banana nuggets, 4,680 greentea flavored drinks and 3,120 cappuccino-flavored drinks.